Community empowerment in stunting prevention and control to build a healthy and productive generation - Indrawati Aris Tyarini; Ari Setiawati; Rasi Rahagia; Yani Maidelwita (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
Stunting is a chronic nutritional problem that significantly impacts children's physical and cognitive development, as well as a long-term effect on the quality of the next generation. This community service aims to empower the community in efforts to prevent and overcome stunting to build a healthy and productive generation. This program is carried out through balanced nutrition education, promotion of exclusive breastfeeding, increased access to good sanitation, and monitoring children's growth and development. The methods used include training Posyandu cadres, counselling pregnant and lactating women, and collaborating with local governments to strengthen health facilities at the village level. The service results showed increased community knowledge and skills in identifying and preventing stunting risk factors. In addition, this program also encourages active community participation in maintaining children's health and the environment. With sustainable empowerment, it is hoped that the stunting rate can be suppressed to create a healthy and productive generation